ANALISIS FAKTOR PENERIMAAN DAN TANTANGAN PENGGUNAAN ELECTRONIC MEDICAL RECORD OLEH PERAWAT DI RUMAH SAKIT: KAJIAN LITERATUR [THE ANALYSIS OF ACCEPTANCE FACTORS AND CHALLENGES IN THE USE OF ELECTRONIC MEDICAL RECORD BY NURSES IN HOSPITALS: A LITERATURE REVIEW] - Talebong, Lorensa Tellang; Wijayanti, Catharina Dwiana (Nursing Current: Jurnal Keperawatan, 2024)
Electronic Medical Records (EMR), also referred to as computer-based medical records, provide a significant obstacle in the implementation of information and communication technologies in different healthcare facilities. Frequently, the implementation of EMR technology leads to a rise in the amount of effort required to manage electronic records. The objective of this study is to identify the factors that influence the acceptance and difficulties encountered by nurses in hospitals when adopting EMR technology. This research methodology involved conducting a study through a comprehensive evaluation of existing literature. The literature database comprised Google Scholar, Pubmed, and Gale Cencage. The selected journals must employ both quantitative and qualitative research methodologies, be available in either Indonesian or English, and had been published within the past five years (2018-2023). Nurses were willing to use electronic medical records (EMR) for recording the nursing process. This was due to the practicality, efficiency, and effectiveness of employing an information system. Additionally, the use of EMR ensured continuity of care and service planning, enhanced patient safety, and reduced the need for repeated examinations. The adoption of Electronic Medical Records (EMR) technology by nurses was impeded by apprehensions over patient safety and privacy, augmented workload, and the potential for errors in documentation. Nurses widely adopted EMR technology in hospitals due to its practicality, efficiency, and effectiveness. Its implementation ensured continuity of care and service planning, enhanced patient safety, and minimizes redundant examinations. Notably, factors such as age, gender, and length of service did not influence its adoption.BAHASA INDONESIA Rekam medis berbasis komputer atau yang lebih dikenal dengan Rekam Medis Elektronik atau Electronic Medical Record (EMR) merupakan salah satu tantangan besar dalam penerapan teknologi informasi dan komunikasi di berbagai pusat pelayanan kesehatan. Seringkali dalam penerapan teknologi EMR terjadi peningkatan beban kerja pada penggunaan catatan berbasis elektronik. Tujuan penelitian ini untuk mengetahui faktor penerimaan dan tantangan penggunanaan teknologi EMR oleh perawat di Rumah Sakit. Metode Penelitian ini menggunakan studi literature review. Database yang digunakan sebagai sumber literature terdiri dari Google Scholar, Pubmed dan Gale Cencage. jurnal yang digunakan adalah yang menggunakan desain penelitian kuantitatif dan kualitatif, full text berbahasa Indonesia ataupun berbahasa Inggris, diterbitkan 5 tahun terakhir (2018-2023). Hasil penelitian Perawat dapat menerima implementasi dari penerapan EMR dalam melakukan pendokumentasian proses keperawatan menggunakan sistem informasi karena faktor Praktis, efisien dan efektif, adanya kontinuitas perawatan dan perencanaan pelayanan serta meningkatkan keselamatan pasien dan mengurangi duplikasi pemeriksaan. Sedangkan faktor yang menjadai tantangan penerimaan teknologi EMR oleh perawat adalah teknologi EMR dapat membuat kesalahan pendokumentasian oleh perawat, keamanan dan privasi pasien, serta menambah beban kerja perawat. Penerapan teknologi EMR di rumah sakit oleh perawat sangat disebabkan karena Teknologi EMR sangat praktis, efisien dan efektif, adanya kontinuitas perawatan dan perencanaan pelayanan serta meningkatkan keselamatan pasien dan mengurangi duplikasi pemeriksaan, sedangkan usia, jenis kelamin dan lama kerja tidak berpengaruh.